PERSEPSI MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS CIPUTRA SURABAYA TERHADAP TANTANGAN DAN REKOMENDASI LAYANAN TELEMEDICINE - Devani, Fransiska Betsi Intan; Ritunga, Imelda; Sekarputri, Cempaka Harsa (Universitas Ciputra Surabaya, 2025)
Telemedicine services are a part of technological developments in health services which make it easier for patients to get treatment. The doctor-patient relationships continue to change and evolve along with the development of technology. It is necessary for doctors to keep up with the technological development and should be able to utilize the information and communication technology to improve the quality of the services. Medical students are expected to be able to prepare themselves to face technological developments, one of which is providing telemedicine services. The goal to be achieved in this research is to identify challenges and recommendations from Ciputra University Faculty of Medicine students regarding readiness for providing the telemedicine services. The method used is descriptive qualitative and uses the cross-sectional approach. The results of data analysis show that the majority of Ciputra University Faculty of Medicine students have knowledge of what telemedicine services are, used, and also studied about the telemedicine services. The results show that Ciputra University Faculty of Medicine students agree that there are challenges and recommendations to telemedicine services. Keywords: medical students, challenge, recommendation, telemedicine services